2007
DOI: 10.1016/j.jacc.2006.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Darbepoetin Alfa on Exercise Tolerance in Anemic Patients With Symptomatic Chronic Heart Failure

Abstract: In patients with symptomatic CHF and anemia, darbepoetin alfa increased and maintained hemoglobin concentrations and improved health-related quality of life. A trend toward increased exercise time but not peak VO2 was observed. (Impact of Darbepoetin Alfa on Exercise Tolerance and Left Ventricular Structure in Subjects With Symptomatic Congestive Heart Failure (CHF) and Anemia; http://clinicaltrials.gov/ct/show/NCT00117234?order = 1; NCT00117234).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 28 publications
(35 reference statements)
2
135
2
7
Order By: Relevance
“…However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings. Indeed, three reports showed that anemia treatment increased exercise performance [21,22,24] while one did not [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings. Indeed, three reports showed that anemia treatment increased exercise performance [21,22,24] while one did not [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the effect of anemia correction, usually by iron and erythropoietin or darbopoietin, on exercise performance, measured either by peak _ VO 2 , exercise tolerance or by distance walked at the 6 min walking test, in both HF and non-HF patients [21][22][23][24][25][26][27][28][29]. However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings. Indeed, three reports showed that anemia treatment increased exercise performance [21,22,24] while one did not [23].…”
Section: Discussionmentioning
confidence: 99%
“…Iron supplementation and treatment with erythropoiesis-stimulating agents (ESAs), or a combination of both, are potentially valuable therapeutic options [26,27].…”
Section: Cardio-renal Anemia Syndromementioning
confidence: 99%
“…A positive correlation has been shown between peak VO2 and serum Hb values [56,57]. The administration of erythropoiesis stimulating agents (ESA) has been related to an improvement in exercise capacity either in patients with renal failure [58] or in patients with HF [22,43,59].…”
Section: Oxygen Uptake In Peripheral Tissuesmentioning
confidence: 99%